1996
DOI: 10.1109/20.538871
|View full text |Cite
|
Sign up to set email alerts
|

HDDR processes in Nd/sub 16/Fe/sub 76-x/Zr/sub x/B/sub 8/ alloys and the production of anisotropic magnets

Abstract: The NDDR-behaviour of a series of as-cast alloys given by the general formula Nd16Fe76.xB8Zrx (01~52.0) has been characterised by hydrogen DTA and resistivity studies. It was found that increasing values of x increased the temperature of disproportionation. Microstructural studies of the Nd16Fe75.5Zr0.5B~ alloy showed that a Zr-Fe containing phase present at the grain boundaries in the cast and disproportionated material is transformed during recombination into a Nd-Zr-Fe containing phase. This work shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The resultant powder proved to be suitable for production both of bonded and of fully dense hot-pressed magnets. A review on fundamental and practical aspects of the HDDR process was given by Gutfleisch and Harris (1996).…”
Section: Hydrogen Decrepitation (Hd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant powder proved to be suitable for production both of bonded and of fully dense hot-pressed magnets. A review on fundamental and practical aspects of the HDDR process was given by Gutfleisch and Harris (1996).…”
Section: Hydrogen Decrepitation (Hd)mentioning
confidence: 99%
“…The general hydrogen absorption and desorption features of Nd 16 Fe 76 B 8 and of Nd 11.8 Fe 82.3 B 5.9 (Nd 2 Fe 14 B) alloys are given in figure 36(a) (Book and Harris 1992, Gutfleisch and Harris 1996. The absence of the Nd-rich grain boundary phase in the stoichiometric alloy causes the disproportionation and recombination rates to be significantly lower (Gutfleisch et al 1994d).…”
Section: Hydrogen Decrepitation (Hd)mentioning
confidence: 99%
“…A short disproportionation time was found to increase the degree of alignment and a high coercivity could be achieved by manipulation of the evacuation procedure, ensuring full recombination while avoiding excessive grain growth in an Nd 16 Fe 75.5 Zr 0.5 B 8 alloy. A remanence of B r = 1.03 T and an intrinsic coercivity of i H c = 775 kA m −1 have been achieved [46].…”
Section: Inducement Of Magnetic Anisotropymentioning
confidence: 91%
“…Work [25,46] in this laboratory differed from the established procedure which uses a well-homogenized, near-stoichiometric, Co-containing alloy, possibly with further additions. It was shown that it is possible to induce anisotropy via the HDDR process in a cast Zrdoped 'Neomax'-type alloy without a prior homogenization step and this has important implications with regard to the economics of production.…”
Section: Inducement Of Magnetic Anisotropymentioning
confidence: 99%
“…3 Recently, significant magnetic anisotropy for NdFeB has been observed with only a small amount of Zr addition. 4,5 The mechanism of this orientational anisotropy remains unclear up to the present time though various authors proposed the possible explanation for the case of Co, Ga, and Zr additives. 6,7 Since a small amount of Zr addition seems to play a key role in evolution of magnetic anisotropy of HDDR treated NdFeB magnet and there are no studies on the direct structural determination of Zr site in Nd 2 Fe 14 B structure during HDDR process, it is important to know the site occupancy of Zr in each stage of HDDR process.…”
Section: Sakuraimentioning
confidence: 92%